Social Work Education and Training in Europe and the Bologna Process - Christine Labonté-Roset (Social Work and Society, 2004)
A short review of the last three decades shows that social work programmes have developed similarly in (almost) all European countries, both in terms of structural and content-related characteristics. Here I would like to focus on the following aspects: Increased academic focus of training, Generalist programme, International/European orientation. Increased academic focus means that social work programmes have been established at uni-versities or comparable higher education institutions, such as universities of applied sciences. The only exception is France where the approximately 150, generally fairly small colleges and the 14 larger instituts regionaux have a hybrid position between vocational colleges and universities and are roughly comparable to academies.